Comparative Study of Tropospheric Scintillation Prediction Models at Covenant University, Ota, Southwest Nigeria - S. A. Akinwumi; T. V. Omotosho; M. R. Usikalu; M. O. Adewusi; O. O. Ometan (Science and Technology: Developments and Applications Vol. 6, 2025)
Knowledge of tropospheric scintillation is an important phenomenon in the design of satellite communication systems especially in the case of signal propagation. Tropospheric scintillation occurrences transpire to be one of the key signal impairments that affect earth-satellite paths in modern earth-space communication systems, most importantly at higher frequency bands (both uplink and downlink). One year of scintillation data from January 2015 to December 2015 extracted from Astra 2E/2F/2G Satellite link measurement installed at Covenant University, Ota (Lat: 6.7o N, Long: 3.23o E) Southwest Nigeria, at an elevation angle of 59.9o and a frequency of 12.245 GHz was used in this study. The analysis and the result were compared with some reputable scintillation prediction models to obtain the best performance model for the Ota region. Evaluation of four existing clear-sky scintillation models namely: ITU-R, Karasawa, Otung and Van de Kamp models have been presented in this study. From the result, it was discovered that the Karasawa model gives the lowest percentage error rate for both fade and enhancement of about 0.57% at 0.1 percent of the time and 6.93% at 0.01 percent of the time respectively and therefore was best found fit for the prediction of propagation impairment for the region. However, the model should be tested further using higher frequency bands such as Ka and V bands to confirm the accuracy of the model. The information provided in this study is useful in fading margin for antenna sizing and performance needed for satellite communication links in the region. The ground measurements from Ota have confirmed that the Karasawa model gave the best prediction for tropospheric scintillation intensity for Ota and its environment.